2004
DOI: 10.1046/j.1398-9995.2003.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adverse reactions to food in Germany – a population study

Abstract: The study gives for the first time information about the point prevalence of both immunological and nonimmunological adverse reactions to food and underlines the relevance of this issue in public health. The data also show that an individualized stepwise approach including provocation tests is mandatory to confirm the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
232
6
21

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(273 citation statements)
references
References 21 publications
(19 reference statements)
14
232
6
21
Order By: Relevance
“…Based on the reported prevalence of wheat food allergy, it may therefore be estimated that up to 0.8% of the population is sensitized to Tri a 36 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reported prevalence of wheat food allergy, it may therefore be estimated that up to 0.8% of the population is sensitized to Tri a 36 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although eosinophil cells protect the body against parasites and other infectious agents, its high levels is also responsible for the allergic reaction and worsen asthma state [41]. Earlier studies have also reported that larger number of patients with asthma had high serum IgE levels [42][43][44]. A study done on female adults showed that IgE molecules play a crucial role in allergic respiratory diseases and possibly cause chronic airway inflammation in asthma through activation of effector's cells via high affinity (Fc RI) or low affinity (Fc RII) IgE receptors46.…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%
“…For instance, 3.5% of the total population in France (Kanny et al, 2001), 3.6% in Germany (Zuberbier et al, 2004), and 3.5 _ 4.0% in the United 2001). It is utilized as a nitrogen source during peanut seedling growth (Maleki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%